PENGARUH SOSIALISASI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PELAKU UMKM SUB SEKTOR MAKANAN RINGAN KABUPATEN MALANG - Lutfia Faizah; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2022)
The purpose of this study was to determine tax socialization, and taxpayer awareness, to taxpayer awareness and individual taxpayer compliance with SMEs in the snack food sub sector, Malang Regency. Determination of the sample in this study using purposive sampling technique, so that it can be determined the number of 100 respondents who meet the criteria. The analytical tool used in this research is multiple linear regression analysis. The results showed that tax socialization and awareness of taxpayers simultaneously had a significant effect on individual taxpayer compliance of snack food MSMEs in Malang district. The variables of tax socialization, and taxpayer awareness have a significant and positive effect on individual taxpayer compliance with snacks MSMEs in Malang Regency.Keywords: Tax Socialization, Taxpayer Awareness, Taxpayer Compliance